Investigation of the variability of anterior chamber scan protocol with Cirrus high definition optical coherence tomography. (15th February 2017) - Tun, Tin A; Tan, Shayne S; Atalay, Eray; Verma, Sushma; Nongpiur, Monisha E; Baskaran, Mani; Aung, Tin; Husain, Rahat
Abstract: Importance: The evaluation of anterior chamber scan of Cirrus optical coherence tomography for routine clinical use. Background: To assess the variability of anterior chamber angle measurements. Design: This was a cross‐sectional study. Participants: Forty subjects aged 40–80 years were included. Methods: One randomly selected eye from 40 subjects was imaged with Cirrus optical coherence tomography (Carl Zeiss Meditec, Dublin, CA) by two different operators (expert vs. non‐expert) with a 15‐min interval for inter‐observer and intra‐observer variability of image acquisition. For image grading, the angle opening distance (AOD750) and the trabecular iris space area (TISA750) of nasal and temporal quadrants were measured with a customized algorithm (ImageJ, NIH, Bethesda, MD) by two different graders in a masked and random fashion. Bland Altman analysis and intraclass correlation coefficient (ICC) were calculated. Main Outcome Measures: ICC and limit of agreements (LOA). Results: There were 15 (37.5%) eyes with closed angles. For inter‐observer variability, the mean difference (95% LOA) of AOD750 for image acquisition and grading were −0.0039 mm (−0.0486, 0.0408) and 0.0011 mm (−0.0228, 0.025), respectively. The mean difference (95% LOA) of AOD750 for intra‐observer variability for image acquisition and grading were 0.0013 mm (−0.0362, 0.0389) and −0.0013 mm (−0.0482, 0.0457), respectively. The ICCs were all ≥0.9. There was no significant difference in measurement variability between open and closed angles ( P > 0.05). Conclusions and Relevance: Anterior chamber scan had low inter‐observer and intra‐observer variability in quantitative evaluation that was not affected by the angle status or the experience of an operator.